Meningkatkan Daya Saing UMKM melalui Analisis SWOT dan NIB - Hidayat, Taufik; Wulandari, Anna; Mulyanto, Heru; Bastanta, Andreas Riski; Muhsoni, Ridwan (Institut Ilmu Sosial dan Manajemen Stiami, 2024)
Micro, Small, and Medium Enterprises (MSMEs) are critical as the backbone of local economies and a source of innovation in this rapidly evolving economic world. MSMEs have great potential but often face problems such as lack of capital, limited market access, and lack of knowledge of business strategies. This activity report discusses the mentoring efforts made to support MSMEs, specifically